Moisture absorption film laminate, and method for manufacturing the same
The moisture-absorbing film laminate, utilizing a photocurable resin composition and ultraviolet curing, addresses the limitations of thermal curing by achieving faster curing, improved adhesion, and enhanced wear and moisture absorption properties.
Patent Information
- Application Number
- JP2023169835
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-29
- Publication Date
- 2025-04-10
AI Technical Summary
Existing moisture-absorbing film laminates require high temperatures and time for thermal curing, leading to poor productivity and insufficient wear resistance, while attempts to improve abrasion resistance through filler addition compromise water absorption properties.
A moisture-absorbing film laminate using a photocurable resin composition with a (meth)acryloyl group-containing siloxane resin and specific (meth)acrylic monomers, cured using ultraviolet rays to achieve faster curing and improved adhesion, scuff resistance, and moisture absorption.
The laminate exhibits excellent moisture absorption and wear resistance, with a water absorption rate of 10 w% or more and 30 w% or less, and a haze change value ΔH of 4 or less after the Taber wear test, indicating effective anti-fog and scratch resistance.
Smart Images

Figure 2025059624000001 
Figure 2025059624000002 
Figure 2025059624000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a moisture-absorbing film laminate, and relates to a laminate having a substrate and, on at least a portion of one surface of the substrate, a cured coating of an active energy ray-curable composition that has excellent adhesion to the substrate and can impart excellent properties such as scratch resistance and moisture absorption. [Background technology]
[0002] In recent years, from the viewpoint of energy saving, there has been a demand for anti-fogging technology that prevents condensation from forming on components such as windows in vehicles such as automobiles, trucks, buses, and trains. In anti-fogging technology, a moisture absorbing film is formed on a component such as a window, and moisture that would otherwise condense is absorbed into the moisture absorbing film, thereby exerting an anti-fogging function.
[0003] Examples of such moisture-absorbing films that have been proposed include a coating composition consisting of a (meth)acrylic resin, a polyol compound, and a polyfunctional isocyanate compound (Patent Document 1), a composition containing a polyvinyl acetal resin (Patent Documents 2 and 3), and a composition consisting of a copolymer, a polyfunctional blocked isocyanate compound, and a surfactant (Patent Document 4). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2019-94468 A [Patent Document 2] JP 2012-117025 A [Patent Document 3] JP 2001-146585 A [Patent Document 4] JP 2016-169288 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, in the prior art documents, the curing is performed at high temperatures and takes a long time, resulting in poor productivity and insufficient abrasion resistance. In order to improve the abrasion resistance, a filler is added, but this reduces the water absorption.
[0006] In view of the above circumstances, an object of the present invention is to provide a moisture-absorbing film laminate that can be photocured using ultraviolet light, which allows curing in a shorter time than thermal curing, and that combines excellent anti-fogging properties and abrasion resistance. [Means for solving the problem]
[0007] As a result of intensive research into achieving the above object, the present inventors have found that the above problems can be solved by the following means different from those in the prior art documents, and have completed the present invention. That is, the present invention provides a laminate having a substrate and a moisture-absorbing film formed on a surface of at least one side of the substrate, the moisture-absorbing film being obtained by curing a photocurable resin composition which contains, as essential components, a siloxane resin (A) having a (meth)acryloyl group, the following three (meth)acrylic monomers (B), (C) and (D), and a photoinitiator, and in which the blending ratio of (A):(B):(C):(D) is 0.1-5:35-55:0.5-10:40-60 by weight, The siloxane resin (A) is represented by the general formula (1) and is mainly composed of a polyorganosilsesquioxane having a cage structure in the structural unit, [ka] (wherein R is an organic functional group having a (meth)acryloyl group, and n is 8, 10, or 12). The (meth)acrylic monomer (B) is a bifunctional monomer represented by general formula (2), [ka] (wherein X is H or a methyl group, and a=1 to 5). The (meth)acrylic monomer (C) is a monofunctional monomer represented by general formula (3), [ka] (wherein X is H or a methyl group, and b is 4 to 15). The (meth)acrylic monomer (D) is a monofunctional monomer represented by general formula (4), [ka] (wherein X is H or a methyl group) The moisture-absorbing film laminate is characterized in that the moisture absorption rate of the moisture-absorbing film is 10 w % or more and 30 w % or less, and the haze change value ΔH of the moisture-absorbing film before and after the Taber abrasion test is 4 or less. Effect of the Invention
[0008] According to the present invention, it is possible to provide an anti-fogging laminate having a moisture absorbing film that has both excellent moisture absorbing properties and abrasion resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Each element constituting the present invention will be described in detail below, but the present invention is not limited to the contents described therein as long as it does not deviate from the gist of the present invention. In this specification, the term "(meth)acrylic" means either or both of "acrylic" and "methacrylic". The same applies to "(meth)acrylate" and "(meth)acryloyl".
[0010] [Laminate] The moisture-absorbing film laminate of the present invention has a substrate and a moisture-absorbing film formed on at least a portion of the surface of the substrate. The moisture-absorbing film may be formed on a portion of the surface of the substrate, may be formed on the entire surface of one side of the substrate, or may be formed on the entire surface of the substrate.
[0011] The substrate is not particularly limited as long as it can form a moisture-absorbing film, and may be made of, for example, an inorganic material, an organic material, or a composite material of an inorganic material and an organic material. Among them, glass with poor moisture absorption is preferable, for example, silicate glass (silicate glass, silicate alkali glass, lead alkali glass, soda-lime glass, potassium-lime glass, barium glass), borosilicate glass, phosphate glass, etc., and plate glass made of these glasses (for example, general plate glass (ordinary plate glass, figured plate glass, polished plate glass, float glass), composite glass, laminated glass, tempered glass, etc.). These may be colorless or colored, but curved laminated glass used as a vehicle window is particularly preferable.
[0012] The siloxane resin (A) having a (meth)acryloyl group is represented by the above general formula (1) and is mainly composed of a polyorganosilsesquioxane having a cage structure in its structural unit (also called a cage-type polyorganosilsesquioxane. Polyorganosilsesquioxane is also called a silsesquioxane). In general formula (1), R is an organic functional group having a (meth)acryloyl group, and n is 8, 10, or 12. Examples of the organic functional group R having a (meth)acryloyl group include groups represented by the following general formula (1a): In formula (1a), m is an integer of 1 to 3, and R1 is a hydrogen atom or a methyl group. [ka]
[0013] The silicone resin (A) has an organic functional group R having a (meth)acryloyl group bonded to a silicon atom in the molecule. Specific examples of the cage-type polyorganosilsesquioxane in which n in general formula (1) is 8, 10, or 12 include the cage structures shown in the following structural formulas (5), (6), and (7), respectively. Note that R in the following formulas is the same as R in general formula (1).
[0014] [ka]
[0015] The siloxane resin (A) can be produced by the method described in JP 2004-143449 A, etc. For example, a silicon compound represented by RSiX3 is hydrolyzed and partially condensed in the presence of a polar solvent and a basic catalyst, and the resulting hydrolysis product is further recondensed in the presence of a non-polar solvent and a basic catalyst to produce the siloxane resin (A). Here, in the silicon compound RSiX3 used as the raw material, R is an organic functional group having a (meth)acryloyl group, specifically a group represented by the above general formula (1a), and X3 represents a hydrolyzable group.
[0016] Preferred specific examples of R include a 3-methacryloxypropyl group, a methacryloxymethyl group, and a 3-acryloxypropyl group. The hydrolyzable group X3 is not particularly limited as long as it is a group having hydrolyzability, and examples thereof include an alkoxy group and an acetoxy group, but an alkoxy group is preferable. Examples of the alkoxy group include a methoxy group, an ethoxy group, an n- or i-propoxy group, or an n-, i- or t-butoxy group. A methoxy group is preferable because it has high reactivity.
[0017] Among the silicon compounds represented by RSiX3, preferred compounds include methacryloxymethyltriethoxysilane, methacryloxymethyltrimethoxysilane, 3-methacryloxypropyltrichlorosilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-acryloxypropyltrimethoxysilane, and 3-acryloxypropyltrichlorosilane. Among them, it is preferable to use 3-methacryloxypropyltrimethoxysilane, which is an easily available raw material.
[0018] Examples of the basic catalyst used in the hydrolysis reaction include alkali metal hydroxides such as potassium hydroxide, sodium hydroxide, and cesium hydroxide, and ammonium hydroxide salts such as tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrabutylammonium hydroxide, benzyltrimethylammonium hydroxide, and benzyltriethylammonium hydroxide. Among these, tetramethylammonium hydroxide is preferably used because of its high catalytic activity. The basic catalyst is usually used as an aqueous solution.
[0019] Regarding hydrolysis reaction conditions, the reaction temperature is preferably 0 to 60°C, more preferably 20 to 40°C. If the reaction temperature is lower than 0°C, the reaction rate is slow and the hydrolyzable groups remain in an unreacted state, resulting in a long reaction time. On the other hand, if the reaction temperature is higher than 60°C, the reaction rate is too fast, so a complex condensation reaction proceeds, and as a result, the hydrolysis product is promoted to have a high molecular weight. In addition, the reaction time is preferably 2 hours or more. If the reaction time is less than 2 hours, the hydrolysis reaction may not proceed sufficiently, and the hydrolyzable groups may remain in an unreacted state. The presence of water is essential for the hydrolysis reaction, and this can be supplied from an aqueous solution of a basic catalyst, or water can be added separately. The amount of water should be at least an amount sufficient to hydrolyze the hydrolyzable group, and is preferably 1.0 to 1.5 times the theoretical amount. In addition, it is necessary to use an organic polar solvent during hydrolysis, and as the organic polar solvent, alcohols such as methanol, ethanol, and 2-propanol, or other organic polar solvents can be used. Preferably, it is a lower alcohol having 1 to 6 carbon atoms that is soluble in water, and more preferably, 2-propanol is used. If a non-polar solvent is used, the reaction system will not be homogenous, the hydrolysis reaction will not proceed sufficiently, and unreacted hydrolyzable groups will remain, which is not preferable.
[0020] After the hydrolysis reaction is completed, water or a water-containing reaction solvent is separated. For the separation of water or a water-containing reaction solvent, a means such as evaporation under reduced pressure can be used. In order to sufficiently remove moisture and other impurities, a means such as adding a non-polar solvent to dissolve the hydrolysis reaction product, washing the solution with saline or the like, and then drying with a drying agent such as anhydrous magnesium sulfate can be used. If the non-polar solvent is separated by a means such as evaporation, the hydrolysis reaction product can be recovered, but if the non-polar solvent can be used as a non-polar solvent for the next reaction, it is not necessary to separate it.
[0021] In the hydrolysis reaction, a condensation reaction of the hydrolyzate occurs along with the hydrolysis. The hydrolysis product accompanied by the condensation reaction of the hydrolyzate is usually a colorless viscous liquid having a number average molecular weight of 1400 to 5000. The hydrolysis product is preferably an oligomer having a number average molecular weight of 1400 to 3000, depending on the reaction conditions, in which most, preferably almost all, of the hydrolyzable groups X are replaced with OH groups, and most, preferably 95% or more, of the OH groups are condensed. The structures of the hydrolysis products are multiple types of cage-type, ladder-type, and random-type silsesquioxanes, and even in compounds having a cage structure, the proportion of a complete cage structure is low, and an incomplete cage structure in which a part of the cage is open is predominant. Therefore, the hydrolysis product obtained by this hydrolysis is further heated in an organic solvent in the presence of a basic catalyst to condense (re-condense) the siloxane bonds, thereby selectively producing a cage-type silsesquioxane.
[0022] Specifically, the reaction is carried out as follows. That is, after the hydrolysis reaction is completed as described above, water or a water-containing reaction solvent is separated, and then a recondensation reaction is carried out in the presence of a non-polar solvent and a basic catalyst. Regarding the reaction conditions of the recondensation reaction, the reaction temperature is preferably in the range of 100 to 200°C, and more preferably 110 to 140°C. If the reaction temperature is too low, sufficient driving force for the recondensation reaction is not obtained, and the reaction does not proceed. If the reaction temperature is too high, the (meth)acryloyl group may undergo a self-polymerization reaction, so it is necessary to suppress the reaction temperature or add a polymerization inhibitor or the like. The reaction time is preferably 2 to 12 hours. The amount of the non-polar solvent used should be sufficient to dissolve the hydrolysis reaction product, and the amount of the basic catalyst used should be in the range of 0.1 to 10 wt% relative to the hydrolysis reaction product.
[0023] The non-polar solvent may be one that is not or barely soluble in water, but is preferably a hydrocarbon solvent. Examples of such a hydrocarbon solvent include non-polar solvents with low boiling points such as toluene, benzene, and xylene. Among them, toluene is preferably used. As the basic catalyst, the basic catalyst used in the above hydrolysis reaction can be used, and examples of the basic catalyst include alkali metal hydroxides such as potassium hydroxide, sodium hydroxide, and cesium hydroxide, and ammonium hydroxide salts such as tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrabutylammonium hydroxide, benzyltrimethylammonium hydroxide, and benzyltriethylammonium hydroxide, but a catalyst soluble in a non-polar solvent such as tetraalkylammonium is preferred.
[0024] The hydrolysis product used in the recondensation is preferably washed with water, dehydrated, and concentrated, but can be used without washing with water or dehydration. Water may be present during this reaction, but it is not necessary to actively add it, and it is better to limit the amount of water to that brought in from the basic catalyst solution. If the hydrolysis product is not sufficiently hydrolyzed, water is required in an amount greater than the theoretical amount required to hydrolyze the remaining hydrolyzable groups, but the hydrolysis reaction is usually sufficiently carried out. After the recondensation reaction, the catalyst is washed away with water and concentrated to obtain a cage-type silsesquioxane mixture in which the number of silicon atoms in the molecule is equal to the number of (meth)acryloyl groups.
[0025] The silsesquioxane mixture thus obtained varies depending on the reaction conditions and the state of the hydrolysis product, but the components are considered to be 70% by weight or more of multiple types of cage-type silsesquioxanes, and the rest are ladder-type and random-bridged silsesquioxanes. Since these are difficult to separate and require a lot of time, in the present invention, it is preferable to use a silsesquioxane containing 70% by weight or more of the cage-type silsesquioxane represented by general formula (1) as the siloxane resin (A) having a (meth)acryloyl group. The components of the multiple types of cage-type silsesquioxane are preferably 10 to 40% by weight of T8 represented by general formula (5), 30 to 50% by weight of T10 represented by general formula (6), and 5 to 20% by weight of T12 represented by general formula (7), and may contain 50% by weight or less of other components. T8 can be separated by precipitating as needle-shaped crystals by leaving the silsesquioxane mixture at 20°C or less. The content of the cage-type silsesquioxane can be confirmed, for example, by using GPC or LC-MS.
[0026] The photocurable resin composition of the present invention is obtained by mixing a siloxane resin (A) having a (meth)acryloyl group with (meth)acrylic monomers (B), (C), and (D) in a weight ratio of (A):(B):(C):(D)=0.1-5:35-55:0.5-10:40-60, and adding a photoinitiator. From the viewpoint of the balance between water absorption and abrasion resistance, the more preferable mixing ratio is (A):(B):(C):(D)=1-5:40-45:3-8:45-55.
[0027] The (meth)acryloyl group-containing siloxane resin (A) used in the present invention may be a mixture of cage-type polyorganosilsesquioxanes T8, T10, and T12, or one or two of the T8 species may be separated or concentrated therefrom. The siloxane resin (A) having a (meth)acryloyl group used in the present invention is not limited to the silicone resin obtained by the above-mentioned production method. The siloxane resin (A) is a polyfunctional (meth)acrylate compound having the same number of (meth)acryloyl groups as n, and by blending it at a certain ratio, a crosslinking reaction proceeds three-dimensionally, and it is expected to have an effect of improving the wear resistance of the moisture-absorbing film. The preferred blending ratio is 0.1 to 5 parts by weight based on the photocurable resin composition. If it is less than 0.1 part by weight, the wear resistance becomes insufficient, and if it is more than 5 parts by weight, the moisture-absorbing film becomes hard and brittle. Since the curing shrinkage also increases, cracks may occur during curing, and the moisture-absorbing film becomes hard, making it difficult to expand by moisture absorption, which may lead to a decrease in water absorption properties. From the viewpoint of improving wear resistance, 1 to 5 parts by weight is more preferred.
[0028] Specifically, the (meth)acrylic monomer (B) used in the present invention is glycerin 1,3-diglycerolate diacrylate or glycerin 1,3-diglycerolate dimethacrylate, which is an acrylic acid or methacrylic acid adduct of a reaction product of glycerin and epichlorohydrin. The (meth)acrylic monomer (B) has three hydroxyl groups and two (meth)acrylic groups in one molecule, and therefore is highly hydrophilic, and is expected to increase the water absorption rate of the hygroscopic film and to provide abrasion resistance by constructing an appropriate crosslinking structure. The blending ratio is preferably 35 to 55 parts by weight relative to the photocurable resin composition. If it is less than 35 parts by weight, the water absorption properties and abrasion resistance will be insufficient, and if it is more than 55 parts by weight, the hygroscopic film may become hard and brittle. A more preferred range is 40 to 50 parts by weight.
[0029] Specifically, the (meth)acrylic monomer (C) used in the present invention is methoxypolyethylene glycol acrylate or methoxypolyethylene glycol methacrylate. b=4 to 15, more preferably 6 to 13 in terms of the balance between water absorption rate and wear resistance. The (meth)acrylic monomer (C) is monofunctional and has multiple ether bonds in one molecule, so it is expected to impart moisture absorption properties and moderate flexibility to the moisture absorption film. The blending ratio is preferably 0.5 to 10 parts by weight based on the photocurable resin composition. If it is less than 0.5 parts by weight, the water absorption properties will be insufficient, and if it is more than 10 parts by weight, it will be too soft and the wear resistance will be insufficient. A more preferred blending ratio is 1 to 8 parts by weight.
[0030] Specifically, the (meth)acrylic monomer (D) used in the present invention is 2-hydroxyethyl methacrylate or 2-hydroxyethyl acrylate. The (meth)acrylic monomer (D) is monofunctional and has one hydroxyl group in one molecule, so it is expected to enhance the moisture absorption properties of the moisture absorption film. The blending ratio is preferably 40 to 60 parts by weight based on the photocurable resin composition. If it is less than 40 parts by weight, the moisture absorption properties will be insufficient, and if it is more than 60 parts by weight, the three-dimensional crosslinking of the moisture absorption film will be insufficient, resulting in a soft film with insufficient abrasion resistance. A more preferred blending ratio is 45 to 55 parts by weight.
[0031] In the photocurable resin composition of the present invention, the amount of the photoinitiator added is preferably in the range of 0.01 to 10 parts by weight per 100 parts by weight of the total of the resin composition (resin components not including water and solvent). If the amount is less than this range, crosslinking becomes insufficient, the elastic modulus decreases, and the desired surface hardness cannot be obtained. On the other hand, even if the amount exceeds this range, further improvement in the reaction rate cannot be expected. More preferably, it is in the range of 5 to 10 parts by weight.
[0032] The photopolymerization initiator is not particularly limited, and a wide variety of general-purpose photopolymerization initiators can be used, but compounds such as acetophenone, benzoyl, benzophenone, thioxanthone, and acylphosphine oxide can be suitably used. Specifically, trichloroacetophenone, diethoxyacetophenone, 1-phenyl-2-hydroxy-2-methylpropan-1-one, 1-hydroxycyclohexyl phenyl ketone, 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one, benzoin methyl ether, benzyl dimethyl ketal, benzophenone, 4,4'-bis(diethylamino)-benzophenone, benzophenone-2-methyl carboxylate, 4-benzoyl-4' Examples of the photopolymerization initiator include 1-methyldiphenyl sulfide, 2-hydroxy-2-methyl-1-phenylpropan-1-one, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methylpropionyl)-benzyl]phenyl}-2-methylpropan-1-one, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one, thioxanthone, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, methylphenyl glyoxylate, camphorquinone, benzil, anthraquinone, Michler's ketone, etc. Also, a photoinitiator assistant or a sensitizer that is effective in combination with the photopolymerization initiator can be used in combination.
[0033] The photocurable resin composition may be diluted with a solvent for the purposes of adjusting the solid content concentration, improving dispersion stability, improving coatability, improving adhesion to a substrate, and the like. The solvent may be an organic solvent, such as alcohols, ketones, ethers, esters, cellosolves, and aromatic compounds.Specific examples include methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, isobutyl alcohol, t-butyl alcohol, benzyl alcohol, 2-methoxyethanol, 2-ethoxyethanol, 2-(methoxymethoxy)ethanol, 2-butoxyethanol, furfuryl alcohol, tetrahydrofurfuryl alcohol, diethylene glycol, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, 1-methoxy-2-propanol, 1-ethoxy-2-propanol, dipropylene glycol, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, tripropylene glycol monomethyl ether, diacetone alcohol, acetone, methyl ethyl ketone, 2-pentanone, 3-pentanone, 2-hexanone, methyl isobutyl ketone, 2-heptanone, 4-heptanone, diisobutyl ketone, cyclohexanone, methylcyclohexanone, acetophenone, diethyl Ether, dipropyl ether, diisopropyl ether, dibutyl ether, dihexyl ether, anisole, phenetole, tetrahydrofuran, tetrahydropyran, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1,2-dibutoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, glycerin ether, methyl acetate, ethyl acetate, propyl acetate, isopropyl acetate, butyl acetate, isobutyl acetate, sec-butyl acetate Examples of organic solvents include ethyl acetate, pentyl acetate, isopentyl acetate, 3-methoxybutyl acetate, 2-ethylbutyl acetate, 2-ethylhexyl acetate, methyl propionate, ethyl propionate, butyl propionate, γ-butyrolactone, 2-methoxyethyl acetate, 2-ethoxyethyl acetate, 2-butoxyethyl acetate, 2-phenoxyethyl acetate, diethylene glycol monoethyl ether acetate, diethylene glycol monobutyl ether acetate, benzene, toluene, and xylene. These organic solvents can be used alone or in combination of two or more.
[0034] To the moisture-absorbing film of the present invention, an ultraviolet absorber or a light stabilizer (ultraviolet stabilizer) can be added for the purpose of improving weather resistance. As the ultraviolet absorber, inorganic oxide fine particles such as titanium oxide, cerium oxide, zirconium oxide, zinc oxide, etc., metal chelate compounds of titanium, zinc, zirconium, etc., and inorganic or organic (partial) hydrolysates and condensates thereof can be used. As examples of organic compounds, compound derivatives whose main skeleton is a hydroxybenzophenone, benzotriazole, cyanoacrylate, or triazine are preferred. In addition, polymers containing these ultraviolet absorbents in the side chain, ultraviolet absorbents having reactive functional groups, silylated ultraviolet absorbents, and (partial) hydrolysis condensates thereof may also be used. Specifically, 2-(2-hydroxy-5-t-butylphenyl)-2H-benzotriazole, 2-[5-chloro-(2H)-benzotriazol-2-yl]-4-methyl-6-(t-butyl)phenol, 2-(2H-benzotriazol-2-yl)6-(1-methyl-1-phenylethyl)-4-(1,1,3,3-tetramethylbutyl)phenol, 2-[4-[(2-hydroxy-3-(2'-ethyl)hexyl)oxy]-2-hydroxyphenyl]4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, (co)polymer of 2-hydroxy-4-(2-acryloxyethoxy)benzophenone, (co)polymer of 2-(2'-hydroxy-5'-methacryloxyethylphenyl)-2H-benzotriazole, etc. Two or more of these ultraviolet absorbers may be used in combination.
[0035] The ultraviolet stabilizer is preferably one having one or more cyclic hindered amine structures in the molecule. Specifically, bis(2,2,6,6-tetramethyl-1-(octyloxy)-4-piperidyl)ester, 3-dodecyl-1-(2,2,6,6-tetramethyl-4-piperidinyl)pyrrolidine-2,5-dione, N-methyl-3-dodecyl-1-(2,2,6,6-tetramethyl-4-piperidinyl)pyrrolidine-2,5-dione, N-acetyl-3-dodecyl-1-(2,2,6,6-tetramethyl-4-piperidinyl)pyrrolidine-2,5-dione, Examples of the ultraviolet stabilizer include rolidine-2,5-dione, bis(2,2,6,6-tetramethyl-4-piperidyl) sebacate, bis(1,2,2,6,6-pentamethyl-4-piperidyl) sebacate, tetrakis(2,2,6,6-tetramethyl-4-piperidyl), 1,2,3,4-butanetetracarboxylate, and tetrakis(1,2,2,6,6-pentamethyl-4-piperidyl). Two or more of these ultraviolet stabilizers may be used in combination.
[0036] In addition to the above-mentioned components, various additives may be added to the photocurable resin composition of the present invention, for example, within the range that does not impair the functions. Examples of various additives include organic / inorganic fillers, plasticizers, flame retardants, heat stabilizers, antioxidants, light stabilizers, UV absorbers, lubricants, antistatic agents, release agents, foaming agents, nucleating agents, colorants, crosslinking agents, dispersing agents, resin components, etc.
[0037] Examples of methods for forming a moisture-absorbing film made of a photocurable resin composition on a substrate include a dripping method, a roller coating method, a bar coating method, a spray coating method, an air knife coating method, a spin coating method, a flow coating method, a curtain coating method, and a dipping method. The coating thickness is adjusted by the solid content concentration, taking into consideration the thickness of the film formed after drying and curing by irradiation with active energy rays.
[0038] When a solvent is used, after coating, it is preferable to remove the solvent by drying etc. The drying temperature is preferably set at a condition that does not cause deformation of the substrate used, and the drying time is preferably 1 hour or less from the viewpoint of productivity.
[0039] The moisture-absorbing film of the present invention can be produced by curing the above-mentioned photocurable resin composition by irradiation with active energy rays such as visible light, ultraviolet light, and electron beams, and preferably by irradiation with ultraviolet light having a wavelength of 10 to 400 nm or visible light having a wavelength of 400 to 700 nm, a cured molded product can be obtained. The wavelength of the light used is not particularly limited, but near ultraviolet light having a wavelength of 200 to 400 nm is particularly preferably used. Examples of lamps used as ultraviolet light generating sources include low-pressure mercury lamps (output: 0.4 to 4 W / cm), high-pressure mercury lamps (40 to 160 W / cm), ultra-high-pressure mercury lamps (173 to 435 W / cm), and metal halide lamps (80 to 160 W / cm).
[0040] The method of obtaining a moisture-absorbing film by irradiation with active energy rays such as light irradiation may be performed either in an oxygen-blocking atmosphere or in the air, but is preferably performed in an oxygen-blocking atmosphere.Specific examples of the method include a method of filling the space to be irradiated with nitrogen and a method of using a laminate film to block oxygen during irradiation.
[0041] From the viewpoint of scratch resistance and adhesion, the thickness of the moisture-absorbing film of the present invention is preferably 1 to 100 μm, more preferably 3 to 50 μm. If it is thinner than 1 μm, the moisture absorption amount of the moisture-absorbing film is small, and the anti-fogging performance of the vehicle window member is lost in a short time. On the other hand, if it is thicker than 100 μm, the moisture absorption amount is large and the anti-fogging performance can be maintained for a long period of time, but the visibility is reduced due to the difference in refractive index with the substrate.
[0042] The moisture-absorbing film laminate of the present invention thus obtained has a moisture-absorbing film with a water absorption rate of 10 wt % or more and 30 wt % or less, and a haze change value ΔH before and after a Taber abrasion test performed with a Taber abrasion wheel CS-10F, a load of 500 g, and a rotation speed of 100 revolutions is 4 or less. EXAMPLES
[0043] Examples of the present invention will be described below. The silicone resin (A) used in the examples was obtained by the method shown in the following synthesis example.
[0044] [Synthesis Example 1] A reaction vessel equipped with a stirrer, a dropping funnel, and a thermometer was charged with 40 ml of 2-propanol (IPA) as a solvent and 5% aqueous tetramethylammonium hydroxide (TMAH solution) as a basic catalyst. 15 ml of IPA and 12.69 g of 3-methacryloxypropyltrimethoxysilane (MTMS: SZ-6300 manufactured by Toray Dow Corning Silicone Co., Ltd.) were placed in the dropping funnel, and the IPA solution of MTMS was dropped at room temperature over 30 minutes while stirring the reaction vessel. After the dropping of MTMS was completed, the mixture was stirred for 2 hours without heating. After stirring for 2 hours, the solvent was removed under reduced pressure and dissolved in 50 ml of toluene. The reaction solution was washed with saturated saline until it became neutral, and then dehydrated with anhydrous magnesium sulfate. The anhydrous magnesium sulfate was filtered off and concentrated to obtain 25.8 g of a hydrolysis product (silsesquioxane). This silsesquioxane was a colorless viscous liquid that was soluble in various organic solvents. Next, 20.65 g of the silsesquioxane obtained above, 82 ml of toluene, and 3.0 g of 10% TMAH aqueous solution were placed in a reaction vessel equipped with a stirrer, Dinstark, and cooling tube, and gradually heated to distill off water. The mixture was further heated to 130°C, and a recondensation reaction was carried out at the reflux temperature of toluene. The temperature of the reaction solution at this time was 108°C. After 2 hours of stirring after the toluene reflux, the reaction was terminated. The reaction solution was washed with saturated saline until it became neutral, and then dehydrated with anhydrous magnesium sulfate. The anhydrous magnesium sulfate was filtered off and concentrated to obtain 18.77 g of the target cage-type silsesquioxane (mixture). The obtained cage-type silsesquioxane (S1) was a colorless viscous liquid that was soluble in various organic solvents. When the reaction product after the recondensation reaction was separated by liquid chromatography and then subjected to mass spectrometry, it was confirmed that the molecular ions with ammonium ions were attached to the molecular structures of the above structural formulas (5), (6), and (7) in which R was a methacryloyl group, and the composition ratio of T8:T10:T12:others was about 2:4:1:3, confirming that it was a silicone resin mainly composed of a cage structure. Note that T8, T10, and T12 correspond to the structures (5), (6), and (7) in which R was a methacryloyl group, respectively.
[0045] [Example 1] As the component (A), A1: the cage-type silicone resin having methacryloyl groups on all silicon atoms obtained in Synthesis Example 1; (B) Component B1: Acrylic acid adduct of reaction product of glycerin and epichlorohydrin (Epoxy Ester 80MFA manufactured by Kyoeisha Chemical Co., Ltd.); [ka] (C) As components, C1: methoxypolyethylene glycol acrylate (n=average 13, AM-130G manufactured by Shin-Nakamura Chemical Co., Ltd.), [ka] (D) As the component, D1: 2-hydroxyethyl methacrylate, [ka] A1, B1, C1, and D1 were mixed in an amount of 3, 50, 2, and 45 parts by weight, respectively. As a photopolymerization initiator, P1: 7.5 parts by weight of 1-hydroxycyclohexylphenyl-ketone (Omnirad184 manufactured by IGM), P2: 0.75 parts by weight of 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one (Omnirad907 manufactured by IGM), S1: 80 parts by weight of propylene glycol monomethyl ether as a solvent, U1: 2-[5-chloro-(2H)-benzotriazol-2-yl]-4-methyl-6-(t-butyl)phenol (TINUVIN384-2 manufactured by BASF) as an ultraviolet absorber, U2: 0.5 parts by weight of bis(1,2,2,6,6-pentamethyl-4-piperidyl)sebacic acid (TINUVIN292 manufactured by BASF) as a light stabilizer, and 0.5 parts by weight of fluorine-based surface conditioner F1 were mixed to obtain a photocurable resin composition.
[0046] Next, the coating was applied to a glass plate treated with a silane coupling agent using a spin coater so that the film thickness after drying would be 15 μm, and then dried for 10 minutes at 60° C. Thereafter, the coating was cured using a metal halide lamp with an integrated exposure of 4000 mJ / cm2 and a curing capacity of 500 mW / cm2 in a nitrogen atmosphere, to obtain a moisture-absorbing film laminate in which a moisture-absorbing film having a thickness of 15 μm was formed on the surface of the glass substrate.
[0047] [Examples 2 to 9, Comparative Examples 1 to 8] A moisture-absorbing film laminate was obtained in the same manner as in Example 1, except that the raw materials, blending ratios, and film thicknesses shown in Table 1 were used. Other abbreviations in the table are as follows. C2: Methoxypolyethyleneglycol acrylate (n=average 9, Shin-Nakamura Chemical Co., Ltd. AM-90G) [ka] C3: Methoxytetraethylene glycol methacrylate (n=4, Shin-Nakamura Chemical M-40G) [ka] Z1: Methoxypolyethyleneglycol acrylate (n=average 23, Shin-Nakamura Chemical Co., Ltd. AM-230G) [ka] Z2: Glycerin dimethacrylate (Kyoeisha Chemical Light Ester G-101P) [ka] Z3: 2-hydroxypropyl methacrylate [ka]
[0048] The various properties were evaluated by the following methods, and the evaluation results are shown in Table 21. [Moisture absorption (anti-fogging)] The water absorption rate of the moisture-absorbing film in each laminate was measured by the following method: the weight of a glass substrate having a moisture-absorbing film (hereinafter referred to as a sample) was measured with a balance in a 20% RH environment, and the weight of the moisture-absorbing film was calculated from the weight of the glass substrate alone, which had been measured in advance. The sample was kept in a constant temperature and humidity environment of 95% RH (set temperature: 30° C.) for 1 to 2 hours, and then the change in weight of the sample was measured with a balance and taken as the amount of water absorbed by the hygroscopic film. The water absorption rate was calculated from the weight of the hygroscopic film and the amount of water absorbed by the hygroscopic film according to the following formula. Water absorption rate (w%) = (amount of water absorbed by the hygroscopic film / weight of the hygroscopic film) x 100 The higher the water absorption rate, the better the moisture absorption. The moisture absorption was evaluated based on the water absorption rate according to the following criteria. ○: Water absorption rate ≧ 10w% ×: Water absorption rate < 10w% [Taber abrasion resistance (scratch resistance)] A Taber abrasion test in accordance with JIS K7204 was carried out using an abrasive wheel CS-10F at a load of 500 g and 100 revolutions, and the Taber abrasion resistance was evaluated based on the haze values before and after the test. ΔH = (haze after Taber abrasion test) - (haze before test) The smaller the ΔH (%), the better the abrasion resistance, and the evaluation was based on the following criteria. ○:0< ΔH ≦4 ×:ΔH > 4 [comprehensive evaluation] The evaluation results of moisture absorption (anti-fogging property) and Taber abrasion property (scratch resistance) were evaluated comprehensively. ◯: The evaluation results for both moisture absorption and abrasion resistance were good (◯). ×: At least one of the evaluation results of moisture absorption and abrasion resistance was poor (×).
[0049] [Table 1]
Claims
1. A laminate having a substrate and a moisture-absorbing film formed on a surface of at least one side of the substrate, the moisture-absorbing film being obtained by curing a photocurable resin composition which contains, as essential components, a siloxane resin (A) having a (meth)acryloyl group, the following three types of (meth)acrylic monomers (B), (C) and (D), and a photoinitiator, and in which the blending ratio of (A):(B):(C):(D) is 0.1-5:35-55:0.5-10:40-60 by weight; The siloxane resin (A) is represented by the general formula (1) and is mainly composed of a polyorganosilsesquioxane having a cage structure in a structural unit, 【Chemistry 1】 (wherein R is an organic functional group having a (meth)acryloyl group, and n is 8, 10, or 12). The (meth)acrylic monomer (B) is a bifunctional monomer represented by general formula (2), 【Chemistry 2】 (wherein X is H or a methyl group, and a is 1 to 5). The (meth)acrylic monomer (C) is a monofunctional monomer represented by general formula (3), 【Chemistry 3】 (wherein X is H or a methyl group, and b is 4 to 15). The (meth)acrylic monomer (D) is a monofunctional monomer represented by general formula (4), 【Chemistry 4】 (wherein X is H or a methyl group). A moisture-absorbing film laminate, characterized in that the moisture absorption rate of the moisture-absorbing film is 10 wt % or more and 30 wt % or less, and the haze change value ΔH of the moisture-absorbing film before and after a Taber abrasion test is 4 or less.
2. 2. The moisture-absorbing film laminate according to claim 1, wherein the moisture-absorbing film contains an ultraviolet absorbing agent and / or a light stabilizer.
3. 2. The moisture-absorbing film laminate according to claim 1, which is used as a window member for a vehicle.
4. A method for producing the moisture-absorbing film laminate according to claim 1, comprising the steps of: A method for producing a moisture-absorbing film laminate, comprising: applying a photocurable composition to a substrate; and irradiating the applied photocurable composition with active energy rays to cure the photocurable composition and form a moisture-absorbing film.
5. 5. The method for producing a moisture-absorbing film laminate according to claim 4, wherein in the step of curing the photocurable composition to form a moisture-absorbing film, the irradiation conditions of the active energy rays are light having a wavelength range of 200 nm or more and 400 nm or less, an illuminance of 200 to 900 mW / cm2, and an integrated light amount of 1000 to 8000 mJ / cm2.
Citation Information
Patent Citations
Antifogging substrate and forming method therefor
JP2001146585A
Anti-fog coated article
JP2012117025A
Antifogging agent composition and antifogging article using the same
JP2016169288A
Coating composition, cured film, and article having the cured film
JP2019094468A